The relationships of school-based sexuality education, sexual knowledge and sexual behaviors-a study of 18,000 Chinese college students - Chunyan Li; Zixi Cheng; Taiwen Wu; Xiao Liang; Junjian Gaoshan; Lihe Li; Ping Hong; Kun Tang (BMC, 2017)
Abstract Background A growing prevalence of unexpected pregnancies and younger age of sexual debut is observed among Chinese young people, while they lack formal sexuality education from schools and parents. It is necessary to measure their knowledge level of sexual and reproductive health, and how such knowledge associates with their sexual behaviors and reproductive health outcomes, which would shed light on the effectiveness of sexuality education in China. Methods An Internet-based questionnaire survey was conducted from January to August, 2015. 130 colleges were selected from eastern, central, and western parts China with a good balance of geographic distributions. The survey link was subsequently delivered to the focal points in each college for voluntary participation, targeting on undergraduates aged 18 ~ 25. Information on demographics, experience of school-based sexuality education (defined as any course introducing information on sexual and reproductive health) and SRH knowledge quiz was collected. Multivariate linear regression and logistic regression were applied to explore the relationship between students' SRH knowledge, sexual behaviors and reproductive health outcomes, such as sexual intercourse (penetrative sex by vaginal or anal), unprotected sex, pregnancy and abortion, etc. Results A total sample of 17,966 Chinese college students (mean age = 20.2, 60.4% female) eventually entered the analysis. Only 55.6% of the respondents self-reported having received sexuality education before, and they scored significantly higher (2.33/4.00) in the SRH knowledge quiz than those who had not (1.75/4.00). Among the sexually experienced students (n = 3639, 20.2%), both males and females with higher SRH knowledge were less likely to report having experience of (partner's) pregnancy or abortion (OR < 1, p < 0.05). In the group of sexually experienced males, those with higher SRH knowledge had a slightly later age of sexual debut (coefficient = 0.28, p < 0.001), and were less likely to have unprotected sex during the last or in most sexual intercourses (OR = 0.82, 95%C.I.: 0.69 ~ 0.96). Conclusion Students' experience of school-based sexuality education may be positively associated with their SRH knowledge level as well as with their sexual behaviors and reproductive health outcomes, but such associations were stronger among males than females. A more effective implementation of school-based sexuality education needs to be scaled up, and a gender-sensitive education strategy to different needs is desirable for SRH promotion among Chinese young people.